Health problems of elderly people in pashupati briddhashram, Kathmandu. - Khanal, Ajala (2008)
ABSTRACT: There are many health problems in old age. Elderly people are vulnerable to physical, social, emotional and socio economic problems. A few studies have been undertaken regarding the elderly people. It is necessary to study their socio-economic and health status to promote and maintain their health status and to make future plans. So the study was concentrated on the health problems of elderly people and the topic "Health problems of elderly people in Pashupati Briddhashram, Kathmandu" was selected. The main objective of this study is to identify the socio-economic and demographic characteristics, health problems (physical and psychological), health related practices of elderly people and to assess existing management system in Pashupati Briddhashram. Pashupati Briddhashram inhabits the elderly people of 230. So, it was possible to study all the population so census was done. An interview schedule was used for the collection of necessary information. The coded data was entered into a computer using Microsoft Office Excel and analysis was done by window based SPSS program. Majority of the elderly people (89.1 percent) at this ashram were suffering from some kind of health problem. The most common disease that affect elderly people were headache (18.3 percent), backache (10 percent), joint pain (26.7 percent), poor eyesight (13.3 percent), blindness (8.4%), partial loss of hearing (5.3 percent), cough/asthma (19.1percent) , gout (20.6 percent) , mood disorder/depression (81.6 percent) and occasional diarrhea, fever and common cold. According to the managerial personnel of the ashram, there is a provision for regular health check up of the elderly at ashram's clinic, with a senior nursing staff and visiting doctors of the clinic provide services once a month. The medicine are provided free of cost. The ashram also provides referral services at the higher centers if needed. The existing health practices of the elderly people regarding food and nutrition, personal hygiene and use of safe drinking water were not satisfactory. From this study, the researcher gives suggestions that the government and non government sector should support such Briddhashrams ensuring nursing care. Furthermore such studies should be conducted at national level.